Newman’s Error Analysis Dalam Geometri Ruang Ditinjau dari Kecerdasan Visual Siswa SMA - Ardina Fahriyanti Maharani; Erlina Prihatnani (Jurnal Cendekia : Jurnal Pendidikan Matematika, 2019)
In solid geometry needed the ability to visualize space that cannot be seen so differences in visual intelligence can trigger errors in solving geometry problems. Therefore, this study aimed to determine the types of errors made by students and the factors that cause errors in working on geometry problems based on Newman's Error Analysis (NEA) in terms of visual intelligence. This research chose the subjects of class XII high school who had studied the material distance points to lines in space with different levels of visual intelligence, namely high and low. The process of collecting data used visual intelligence test questions, geometry test questions, and interviews. The results of this study indicated that the level of students' visual intelligence affects the difference in location and the factor that causes errors in the stage of transformation especially on determining the distance in dimension 3. Students with high visual intelligence made mistakes at the stage of transformation and encoding that caused by the students’ carelessness. However, students with low visual intelligence made mistakes at the stage of comprehension, transformation, process skills, and encoding due to the concept of the point distance to the line and the concept of the Pythagorean theorem.